Hu proteins regulate alternative splicing by inducing localized histone hyperacetylation in an RNA-dependent manner - Zhou, Hua-Lin (National Academy of Sciences, 2011)
Recent studies have provided strong evidence for a regulatory link among chromatin structure, histone modification, and splicing regulation. However, it is largely unknown how local histone modification patterns surrounding alternative exons are connected to differential alternative splicing outcomes. Here we show that splicing regulator Hu proteins can induce local histone hyperacetylation by association with their target sequences on the pre-mRNA surrounding alternative exons of two different genes. In both primary and mouse embryonic stem cell-derived neurons, histone hyperacetylation leads to an increased local transcriptional elongation rate and decreased inclusion of these exons. Furthermore, we demonstrate that Hu proteins interact with histone deacetylase 2 and inhibit its deacetylation activity. We propose that splicing regulators may actively modulate chromatin structure when recruited to their target RNA sequences cotranscriptionally. This “reaching back” interaction with chromatin provides a means to ensure accurate and efficient regulation of alternative splicing.